Composite alloy casting and preparation method thereof
Through the composite process of extruded deformation components and die-cast molded components, combined with the surface treatment of semi-solid aluminum alloy paste, the problem of defects in anodizing of traditional aluminum alloy frames and difficulty in manufacturing variable cross-sectional workpieces is solved, achieving high-quality surfaces and the manufacturing of complex shapes reduces processing difficulty.
Patent Information
- Application Number
- CN202411348799.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional aluminum alloy frames are prone to defects such as different colors and flow marks during the anodization process, and it is difficult to produce variable-section workpieces in the extrusion deformation process, which cannot meet the needs of mobile phone frames for high-quality appearance and complex shapes.
The composite process of extruded deformation components and die-cast molded components is adopted to provide high-quality appearance through extruded deformation components, and the die-casting process is used to produce complex variable cross-sectional workpieces, combined with semi-solid aluminum alloy paste for surface treatment to improve interface bonding.
The anodizing effect without different colors and flow marks and the manufacturing of complex shapes is achieved, which solves the problem that it is difficult to prepare variable-section workpieces and die-casting molding methods and difficult to obtain high-quality surfaces, reducing the difficulty of processing.
Smart Images

Figure CN119140628A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal composite materials and processing thereof, in particular to a composite alloy casting and a preparation method thereof. Background Art
[0002] With the growing demand for thinner and lighter phones with higher screen-to-body ratios, the requirements for phone frames are gradually increasing. Aluminum alloy frames, with their thinness and high strength, are being adopted by an increasing number of mobile phone manufacturers. Traditional die-cast aluminum alloys exhibit a certain degree of air entrainment after high-pressure die-casting. Even after CNC machining, surface defects remain to a greater or lesser extent, resulting in poor anodizing results. Deformed aluminum alloys, however, experience segregation during the extrusion casting process, which leads to poor anodizing and appearance defects such as discoloration and flow marks. Therefore, casting processes struggle to meet the desired appearance requirements for frames. Extrusion deformation is not suitable for producing frames with variable cross-sections, as most frames are cast in variable cross-sections.
[0003] Therefore, it is necessary to provide a composite alloy casting and a preparation method thereof. Summary of the Invention
[0004] A first aspect of the present invention provides a composite alloy casting, characterized in that it comprises an extrusion deformation component and a die-casting component, the extrusion forming component comprises an appearance surface and a composite surface, and the die-casting component is combined with the composite surface.
[0005] This solution uses an extrusion deformation component and a die-casting molding component for compounding. The extrusion deformation component is obtained by extrusion deformation of the blank, and is not prone to segregation problems. Its appearance surface can obtain a high-quality surface during surface treatment. For example, there will be no defects such as discoloration and marks during anodizing. Moreover, the appearance surface is provided by the extrusion deformation component, so there is no need to consider the problem that the die-casting molding component still has surface defects after CNC processing; the die-casting molding component is obtained by the die-casting process, and the die-casting process can be used to produce complex variable-section workpieces, while the extrusion deformation process can generally only produce workpieces of equal cross-section. Therefore, by compounding the die-casting molding component on the extrusion deformation component, it can be used to produce composite alloy castings with variable cross-sections. Therefore, the above method not only solves the problem that the extrusion forming method is difficult to apply to the preparation of variable-section workpieces, but also solves the problem that the die-casting molding method is difficult to obtain a high-quality surface.
[0006] Furthermore, the die-cast component is made of A356 aluminum alloy. The composition of A356 aluminum alloy is as follows: Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder is aluminum.
[0007] Furthermore, the material of the extrusion deformation component is 6 series aluminum alloy, which has a good anodizing effect.
[0008] Furthermore, the thermal expansion coefficient of the material of the extruded component is α, and the thermal expansion coefficient of the material of the die-cast component is (0.98~1.02)α. Specifically, it can be between 0.99, 1.00, and 1.01. By controlling the ratio of the thermal expansion coefficients of the materials of the extruded component and the die-cast component, cracking caused by shrinkage during the heat treatment process can be avoided. Specifically, the thermal expansion coefficient of 6013 aluminum alloy is 23.6*10 -6 / K, while the thermal expansion coefficient of A356 is 23.2*10 -6 / K, the latter is 0.983 times of the former.
[0009] Furthermore, the material of the die-cast component is A356 aluminum alloy, and the material of the extruded component is 6013 aluminum alloy. The thermal expansion coefficients of A356 aluminum alloy and 6013 aluminum alloy are similar, which can avoid cracking caused by shrinkage during subsequent heat treatment. Furthermore, the composition of 6013 aluminum alloy is as follows: Si: 0.84%, Fe: 0.11%, Mg: 0.918%, Cu: 0.7696%, Mn: 0.317%, Zn: 0.021%, Ti: 0.0054%, Cr: 0.0123%, and the remainder is aluminum.
[0010] Furthermore, the composite surface undergoes a surface treatment, and the surface treatment comprises forming micropores, microgrooves, protrusions and / or pits on the composite surface by laser, etching, wire cutting and / or roughening. After the surface treatment, the surface roughness of the composite surface is Ra 0.05-0.15 mm and Rz 0.2-0.5 mm. Through the surface treatment, the composite surface forms the above structure. During the extrusion casting process, the slurry can penetrate into the above structure to form a physical fit, thereby improving the interface bonding force. Furthermore, an array of diamond-shaped protrusions is formed on the composite surface by laser processing.
[0011] Furthermore, the composite surface undergoes secondary surface treatment, and the secondary surface treatment step includes: uniformly pouring a semi-solid aluminum alloy slurry with a solid phase fraction of 50-70% onto the composite surface that has undergone the primary surface treatment, and the volume of the semi-solid alloy slurry is the area of the composite surface*(0.1-0.5) mm. The semi-solid alloy slurry with the aforementioned solid fraction exhibits laminar flow characteristics and can be evenly distributed on the composite surface. The solid phase particles and a small amount of liquid phase in the semi-solid slurry can form a semi-solid layer with a physically interlocking structure with the micropores, microgrooves, protrusions, and / or pits on the composite surface. Furthermore, gas in the thin semi-solid layer easily escapes. During subsequent extrusion casting to form a die-cast component on the composite surface, the liquid or semi-solid alloy melt is injected into the mold. The primary phase of the surface-solidified semi-solid layer reverts to solid particles, while other low-melting-point phases melt and mix with the liquid phase of the alloy melt, solidifying into one during the die-casting process. This improves interfacial bonding strength and reduces the liquid phase fraction at the interface between the composite surface and the melt, preventing shrinkage cavities caused by excessively high liquid phase fractions at the interface and further improving interfacial bonding strength. The solid fraction can be selected between 50%, 55%, 60%, 65%, and 70%.
[0012] Furthermore, the semi-solid alloy slurry and the die-casting component have the same composition, which can avoid excessive differences in thermal expansion properties due to different compositions, thereby preventing shrinkage cracking.
[0013] Furthermore, the composite alloy casting is a frame. Frames have high requirements for casting surface quality, and many frames are workpieces with variable cross-sections. Using the above casting as a frame can reduce the difficulty of frame processing. Specifically, when the composite alloy casting is a frame, a frame (i.e., an extrusion deformation component) is first formed through an extrusion deformation process. The outer side of the frame serves as the exterior surface, which provides a better visual effect. The inner side of the frame serves as the composite surface, and a die-cast component is formed on the inner side of the frame through an extrusion casting process.
[0014] The second aspect of the present invention provides a method for preparing a composite alloy casting, comprising the following steps: processing an extruded aluminum alloy according to the shape of the casting to obtain the extruded deformed component, fixing the extruded deformed component to the movable mold of the mold, melting the die-cast aluminum alloy to form a die-cast aluminum alloy melt, and injecting the die-cast aluminum alloy melt into the mold for extrusion casting on the composite surface to form the die-cast component.
[0015] The casting obtained by the above preparation method has both excellent surface quality and reduced processing difficulty.
[0016] Furthermore, the parameters of the squeeze casting are: filling speed of 150-200 mm / s, casting pressure of 140-190 MPa, mold temperature of 300-350° C., and holding time of 10-30 seconds. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of a casting according to an embodiment.
[0018] Figure 2 This is a schematic diagram of the appearance of the anodized casting of Example 1.
[0019] Figure 3 Schematic diagram of the casting bonding state of Example 1.
[0020] Figure 4 This is a microscope image of a cross section of the casting of Example 1.
[0021] Figure 5 This is a metallographic image of a cross section of the casting of Example 1.
[0022] Figure 6 This is a metallographic image of the composite surface of the casting of Example 1. DETAILED DESCRIPTION
[0023] For ease of understanding of the present application, the present application will be described more fully below. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0024] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of such features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of this application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0026] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0027] In this application, when referring to numerical ranges, unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges subsumed therein.
[0028] Unless otherwise specified, the percentage contents mentioned in this application refer to mass percentage for solid-liquid mixture and solid-solid mixture, and refer to volume percentage for liquid-liquid mixture.
[0029] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0030] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows for temperature fluctuations within the precision range of instrument control.
[0031] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape but may be irregular, primary or secondary. The particle size of irregular particles is the average of their maximum and minimum diameters.
[0032] like Figure 1 FIG2 is a schematic diagram of a casting according to an embodiment. The casting is a frame 100, comprising an outer surface 10 and an inner surface 20. The outer surface 10 is the area visible to the user after the frame 100 is assembled into a finished product, while the inner surface 20 is the area not visible to the user after the frame 100 is assembled into a finished product.
[0033] Example 1: An extruded 6013 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined in the thick wall of the frame to ensure quick and easy placement of the frame in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is, by weight, 0.84% Si, 0.11% Fe, 0.918% Mg, 0.7696% Cu, 0.317% Mn, 0.021% Zn, 0.0054% Ti, 0.0123% Cr, with the remainder being aluminum.
[0034] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. Laser processing technology creates an array of diamond-shaped protrusions on the inner surface, with a roughness of 0.05mm Ra and 0.35mm Rz. The composite surface is cleaned with commercially available aluminum alloy deashing agent, aluminum alloy degreaser, and acidic alumina remover. After cleaning, rinse with clean water, blow dry with a hair dryer, and store for future use. The outer frame is placed in a mold at 340°C. Heat transfer from the mold is used to raise the temperature. When the outer frame reaches 220°C, the mold is closed and die-cast.
[0035] The A356 aluminum alloy is heated to melt and then kept at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy is as follows: in terms of mass fraction, Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder is aluminum.
[0036] A356 melt was injected into the mold at a filling speed of 180 mm / s, a casting pressure of 180 MPa, a holding time of 20 s, and a mold temperature of 340° C. The obtained frame was subjected to T6 heat treatment.
[0037] Example 2: An extruded 6013 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined in the thick wall of the frame to ensure quick and easy placement of the frame in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame (filling the mold) to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is, by weight, 0.84% Si, 0.11% Fe, 0.918% Mg, 0.7696% Cu, 0.317% Mn, 0.021% Zn, 0.0054% Ti, 0.0123% Cr, with the remainder being aluminum.
[0038] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. The composite surface is treated by etching to a roughness of 0.14mm Ra and 0.46mm Rz. The composite surface is cleaned with commercially available aluminum alloy deashing agents, aluminum alloy degreasers, and acidic alumina removers. After cleaning, rinse with clean water, dry with a hairdryer, and store for later use. The outer frame is placed in a mold heated to 340°C. Heat is transferred from the mold to the outer frame, and when the temperature reaches 220°C, the mold is closed for die casting.
[0039] The A356 aluminum alloy is heated to melt and then kept at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy is as follows: in terms of mass fraction, Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder is aluminum.
[0040] A356 melt was injected into the mold at a filling speed of 180 mm / s, a casting pressure of 180 MPa, a holding time of 20 s, and a mold temperature of 340° C. The obtained frame was subjected to T6 heat treatment.
[0041] Example 3: An extruded ADC12 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined into the thick wall of the frame to ensure quick and easy placement in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame (filling the mold) to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the ADC12 aluminum alloy is, by weight, 10.5% Si, 0.9% Fe, 0.20% Mg, 2.0% Cu, 0.35% Mn, 0.72% Zn, with the remainder being aluminum.
[0042] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. Laser processing technology creates an array of diamond-shaped protrusions on the inner surface, with a roughness of 0.05mm Ra and 0.35mm Rz. The composite surface is cleaned with commercially available aluminum alloy deashing agent, aluminum alloy degreaser, and acidic alumina remover. After cleaning, rinse with clean water, blow dry with a hair dryer, and store for future use. The outer frame is placed in a mold at 340°C. Heat transfer from the mold is used to raise the temperature. When the outer frame reaches 220°C, the mold is closed and die-cast.
[0043] The A356 aluminum alloy is heated to melt and then kept at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy is as follows: in terms of mass fraction, Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder is aluminum.
[0044] A356 melt was injected into the mold at a filling speed of 180 mm / s, a casting pressure of 180 MPa, a holding time of 20 s, and a mold temperature of 340° C. The obtained frame was subjected to T6 heat treatment.
[0045] Example 4: An extruded 6013 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined in the thick wall of the frame to ensure quick and easy placement of the frame in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame (filling the mold) to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is, by weight, 0.84% Si, 0.11% Fe, 0.918% Mg, 0.7696% Cu, 0.317% Mn, 0.021% Zn, 0.0054% Ti, 0.0123% Cr, and the remainder being aluminum.
[0046] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. Laser processing technology creates an array of diamond-shaped protrusions on the inner surface, with a roughness of 0.05mm Ra and 0.35mm Rz. The composite surface is cleaned with commercially available aluminum alloy deashing agent, aluminum alloy degreaser, and acidic alumina remover. After cleaning, rinse with clean water, blow dry with a hair dryer, and store for future use. The outer frame is placed in a mold at 340°C. Heat transfer from the mold is used to raise the temperature. When the outer frame reaches 220°C, the mold is closed and die-cast.
[0047] An A356 aluminum alloy was melted and held at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy is, by mass, 7.10% Si, 0.11% Fe, 0.33% Mg, 0.0013% Cu, 0.0042% Mn, 0.0123% Zn, 0.1005% Ti, 0.0037% Ni, 0.0039% Pb, and 0.0032% Sn, with the remainder being aluminum. The A356 melt was then prepared by electromagnetic stirring to form an A356 semi-solid melt with a solid phase fraction of 30%.
[0048] A356 semi-solid melt was injected into the mold at a filling speed of 150 mm / s, a casting pressure of 140 MPa, a holding time of 30 s, and a mold temperature of 300° C. The obtained frame was subjected to T6 heat treatment.
[0049] Example 5: An extruded 6013 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined in the thick wall of the frame to ensure quick and easy placement of the frame in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is, by weight, Si: 0.84%, Fe: 0.11%, Mg: 0.918%, Cu: 0.7696%, Mn: 0.317%, Zn: 0.021%, Ti: 0.0054%, Cr: 0.0123%, with the remainder being aluminum.
[0050] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. Laser processing technology creates an array of diamond-shaped protrusions on the inner surface, with a roughness of 0.05mm Ra and 0.35mm Rz. The composite surface is cleaned with commercially available aluminum alloy de-ashing agent, aluminum alloy de-greaser, and acidic aluminum oxide remover. After cleaning, rinse with clean water, dry with a hair dryer, and store until ready for use. The outer frame is placed in a mold heated to 340°C, where heat transfer from the mold increases the temperature.
[0051] A356 aluminum alloy was melted and held at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy was as follows: Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder was aluminum. 20 mL of the A356 melt was prepared by electromagnetic stirring to form an ADC semi-solid melt with a solid fraction of 50%. The remaining A356 melt was also prepared by electromagnetic stirring to form an A356 semi-solid melt with a solid fraction of 30%. The ADC semi-solid melt with a solid fraction of 70% was uniformly poured onto the surface of the composite surface, with an area of 100 cm. 2 The pouring volume is 5 mL, and when the outer frame temperature reaches 220°C, the mold is closed and die-casting is carried out.
[0052] A semi-solid melt of A356 with a solid fraction of 30% was injected into the mold at a filling speed of 150 mm / s, a casting pressure of 140 MPa, a holding time of 30 seconds, and a mold temperature of 300°C. The obtained frame was subjected to T6 heat treatment.
[0053] Example 6: An extruded 6013 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined in the thick wall of the frame to ensure quick and easy placement of the frame in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame (filling the mold) to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is as follows: Si: 0.84%, Fe: 0.11%, Mg: 0.918%, Cu: 0.7696%, Mn: 0.317%, Zn: 0.021%, Ti: 0.0054%, Cr: 0.0123%, with the remainder being aluminum.
[0054] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. Laser processing technology creates an array of diamond-shaped protrusions on the inner surface, with a roughness of 0.05mm Ra and 0.35mm Rz. The composite surface is cleaned with commercially available aluminum alloy de-ashing agent, aluminum alloy de-greaser, and acidic aluminum oxide remover. After cleaning, rinse with clean water, dry with a hair dryer, and store until ready for use. The outer frame is placed in a mold heated to 340°C, where heat transfer from the mold increases the temperature.
[0055] A356 aluminum alloy was melted and held at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy was as follows: Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder was aluminum. 20 mL of the A356 melt was prepared by electromagnetic stirring to form an ADC semi-solid melt with a solid fraction of 60%. The remaining A356 melt was also prepared by electromagnetic stirring to form an A356 semi-solid melt with a solid fraction of 30%. The ADC semi-solid melt with a solid fraction of 70% was uniformly poured onto the surface of the composite surface, with an area of 100 cm. 2 The pouring volume is 1 mL, and when the outer frame temperature reaches 220°C, the mold is closed and die-casted.
[0056] A semi-solid melt of A356 with a solid fraction of 30% was injected into the mold at a filling speed of 150 mm / s, a casting pressure of 140 MPa, a holding time of 30 seconds, and a mold temperature of 300°C. The obtained frame was subjected to T6 heat treatment.
[0057] Example 7: An extruded 6013 aluminum alloy profile frame was machined using CNC according to the design drawings. Two support holes were machined in the thick wall of the frame to ensure quick and easy placement of the frame in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame (filling the mold) to allow for the machining of the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is, by weight, 0.84% Si, 0.11% Fe, 0.918% Mg, 0.7696% Cu, 0.317% Mn, 0.021% Zn, 0.0054% Ti, 0.0123% Cr, with the remainder being aluminum.
[0058] The outer frame consists of an inner and outer surface. The inner surface serves as the composite surface, while the outer surface serves as the exterior finish. Laser processing technology creates an array of diamond-shaped protrusions on the inner surface, with a roughness of 0.05mm Ra and 0.35mm Rz. The composite surface is cleaned with commercially available aluminum alloy de-ashing agent, aluminum alloy de-greaser, and acidic aluminum oxide remover. After cleaning, rinse with clean water, dry with a hair dryer, and store until ready for use. The outer frame is placed in a mold heated to 340°C, where heat transfer from the mold increases the temperature.
[0059] A356 aluminum alloy was melted and held at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy was as follows: Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder was aluminum. 20 mL of the A356 melt was prepared by electromagnetic stirring to form an ADC semi-solid melt with a solid fraction of 70%. The remaining A356 melt was also prepared by electromagnetic stirring to form an A356 semi-solid melt with a solid fraction of 30%. The ADC semi-solid melt with a solid fraction of 70% was uniformly poured onto the surface of the composite surface, with an area of 100 cm. 2 The pouring volume is 5 mL, and when the outer frame temperature reaches 220°C, the mold is closed and die-casting is carried out.
[0060] A semi-solid melt of A356 with a solid fraction of 30% was injected into the mold at a filling speed of 150 mm / s, a casting pressure of 140 MPa, a holding time of 30 seconds, and a mold temperature of 300°C. The obtained frame was subjected to T6 heat treatment.
[0061] Comparative Example 1: An extruded 6013 aluminum alloy profile frame was CNC-machined according to the design drawings. Two support holes were machined into the thick wall of the frame to ensure quick and easy placement in the mold and prevent it from falling during mold movement. A protrusion (serving as the thick wall) was formed at the distal end of the frame to allow for the 4mm Ø support holes. The holes were non-penetrating to prevent molten aluminum from entering and causing jamming. The composition of the 6013 aluminum alloy is, by weight, 0.84% Si, 0.11% Fe, 0.918% Mg, 0.7696% Cu, 0.317% Mn, 0.021% Zn, 0.0054% Ti, 0.0123% Cr, with the remainder being aluminum.
[0062] The outer frame consists of an inner surface and an outer surface, with the inner surface serving as the composite surface and the outer surface as the exterior surface. The composite surface is cleaned with commercially available aluminum alloy dust remover, aluminum alloy degreaser, and acidic aluminum oxide remover. After cleaning, rinse with clean water, blow dry with a hairdryer, and store for later use. The outer frame is placed in a mold at 340°C, where heat transfer from the mold increases the temperature. When the outer frame reaches 220°C, the mold is closed for die casting.
[0063] The A356 aluminum alloy is heated to melt and then kept at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy is as follows: in terms of mass fraction, Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder is aluminum.
[0064] A356 melt was injected into the mold at a filling speed of 180 mm / s, a casting pressure of 180 MPa, a holding time of 20 s, and a mold temperature of 340° C. The obtained frame was subjected to T6 heat treatment.
[0065] Comparative Example 2: An A356 aluminum alloy was heated to melt and kept warm at 650°C to obtain an A356 melt. The composition of the A356 aluminum alloy was as follows: in terms of mass fraction, Si: 7.10%, Fe: 0.11%, Mg: 0.33%, Cu: 0.0013%, Mn: 0.0042%, Zn: 0.0123%, Ti: 0.1005%, Ni: 0.0037%, Pb: 0.0039%, Sn: 0.0032%, and the remainder was aluminum.
[0066] A356 melt was injected into the frame mold at a filling speed of 180 mm / s, a casting pressure of 180 MPa, a holding time of 20 seconds, and a mold temperature of 340°C. The surface of the frame closest to the upper mold was used as the surface. The resulting frame was subjected to T6 heat treatment.
[0067] The frames obtained in Examples 1-7 and Comparative Examples 1-2 were tested. The bonding strength test method was as follows (testing was performed with reference to the peeling method in GJB446-1988, where the peeling strength is the interface bonding strength of this embodiment). Surface quality testing was performed after the surface was CNC-treated and anodized, yielding the following table.
[0068] Table 1 According to the data in Table 1 and Figure 2It can be seen that the interface bonding strength of Examples 1-2 and Examples 4-7 is higher than that of Comparative Example 1, and the surface quality of Examples 1-7 is higher than that of Comparative Example 2. This is because the present solution uses an extrusion deformation component and a die-casting molding component for compounding. The extrusion deformation component is obtained by extruding and deforming the blank, and is not prone to segregation problems. Its appearance surface can obtain a high-quality surface when subjected to surface treatment. For example, defects such as discoloration and marks will not appear during anodizing. Moreover, the appearance surface is provided by the extrusion deformation component, so there is no need to consider the problem that the die-casting molding component still has surface defects after CNC processing; the die-casting molding component is obtained by the die-casting process, and the die-casting process can be used to produce complex variable-section workpieces, while the extrusion deformation process can generally only produce workpieces of equal cross-section. Therefore, by compounding the die-casting molding component on the extrusion deformation component, it can be used to produce composite alloy castings with variable cross-sections. Therefore, the above method not only solves the problem that the extrusion forming method is difficult to apply to the preparation of variable-section workpieces, but also solves the problem that the die-casting molding method is difficult to obtain a high-quality surface. Figure 2 The casting has no cracks on the surface, no discoloration on the anode and no flow marks. Figure 3 This is a schematic diagram of the combined state of the castings of Example 1, where it can be seen that the die-casting component is combined with the composite surface of the extrusion component. Figure 4 This is a microscope image of a section of the casting of Example 1. Figure 5 This is a metallographic image of a cross section of the casting of Example 1, from which it can be seen that a physical interlocking structure is formed between the extrusion-molded component and the die-casting component. Figure 6 The metallographic diagram of the composite surface of the casting of Example 1 shows that a physical interlocking structure is formed between the extrusion forming component and the die-casting forming component, and the metallographic phase of the die-casting forming component is a crystal formed by liquid phase solidification. In addition, the cross-sectional bonding strength of Example 3 is not as good as that of other embodiments, and obvious cracking occurs. This is because it uses the ADC12 extruded deformation aluminum alloy with a large difference in thermal expansion coefficient from A356, and cracking occurs during the heat treatment process. This shows that when preparing some composite castings that require heat treatment, it is necessary to select two materials with a small difference in thermal expansion coefficient as the materials for the extrusion deformation component and the die-casting forming component. Of course, in some scenarios where heat treatment is not required, it is also allowed to use two materials with different thermal expansion coefficients to prepare composite alloy castings using the above method.
[0069] The interface bonding strength of Example 4 is higher than that of Example 1 because it uses a semi-solid A356 melt, and the solid phase particles in the melt can further improve the interface bonding strength. The cross-sectional bonding strength of Example 5-7 is higher than that of Example 4 because semi-solid slurries with too high a solid phase fraction cannot be used in the die-casting process, and semi-solid slurries with low solid phase fractions are prone to form shrinkage holes in the interface layer during the solidification process, resulting in reduced interface bonding strength; while Example 5-7 uses a semi-solid slurry with a high solid phase fraction to treat the composite layer in advance, and the solid phase particles of the semi-solid slurry are embedded in the rough surface of the composite layer, forming a thin semi-solid layer on the surface of the composite layer. The bubbles in the semi-solid layer are also easy to escape, so the semi-solid layer is not easy to Shrinkage cavities are generated. When the die-casting component is formed on the composite surface by subsequent extrusion casting, the liquid or semi-solid alloy melt is filled into the mold by injection, and the primary phase of the semi-solid layer solidified on the surface is restored to solid particles, while other phases with low melting points melt and mix with the liquid phase of the alloy melt, and solidify into one during the die-casting process, thereby improving the interface bonding strength. The primary phase with more primary phases distributed at the interface can reduce the liquid phase fraction at the interface between the composite surface and the melt, and prevent shrinkage cavities caused by excessively high liquid phase fractions at the interface, thereby improving the interface bonding strength. The interface bonding strength of Example 6 is further improved compared to that of Examples 4 and 5. This is because it uses a preferred solid phase fraction. If the solid phase fraction is too low, the intercalation of the semi-solid layer will be reduced and the number of shrinkage cavities will increase; if the solid phase fraction is too high, the semi-solid layer will be difficult to be evenly distributed on the composite surface, thus preventing the interface bonding strength from being further improved.
[0070] Example 2 uses another one-time surface treatment method and still achieves better results.
[0071] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0072] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.
Claims
1. A composite alloy casting, characterized in that: It comprises an extrusion deformation component and a die-casting component. The extrusion forming component comprises an appearance surface and a composite surface. The die-casting component is formed on the composite surface by an extrusion casting process.
2. The composite alloy casting according to claim 1, characterized in that: The material of the die-casting component is A356 aluminum alloy.
3. The composite alloy casting according to claim 1, characterized in that: The material of the extrusion deformation component is 6 series aluminum alloy.
4. The composite alloy casting according to claim 1, characterized in that: The thermal expansion coefficient of the material of the extrusion deformation component is α, and the thermal expansion coefficient of the material of the die-casting component is (0.98~1.02)α.
5. The composite alloy casting according to claim 1, characterized in that: The material of the die-casting component is A356 aluminum alloy, and the material of the extrusion deformation component is 6013 aluminum alloy.
6. The composite alloy casting according to claim 1, characterized in that: The composite surface is subjected to a surface treatment, and the surface treatment comprises: forming micropores, microgrooves, protrusions and / or pits on the composite surface by laser, etching, wire cutting and / or roughening. After the surface treatment, the surface roughness of the composite surface is Ra 0.05-0.15 mm and Rz is 0.2-0.5 mm.
7. The composite alloy casting according to claim 6, characterized in that: The composite surface undergoes secondary surface treatment, and the secondary surface treatment step comprises: uniformly pouring a semi-solid alloy slurry with a solid phase fraction of 50-70% onto the composite surface that has undergone the primary surface treatment, and the volume of the semi-solid alloy slurry is the area of the composite surface*(0.1-0.5) mm.
8. The composite alloy casting according to claim 1, characterized in that: The composite alloy casting is a frame.
9. A method for preparing a composite alloy casting according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: processing the extruded aluminum alloy according to the shape of the casting to obtain the extruded deformation component, fixing the extruded deformation component to the movable mold of the mold, melting the die-cast aluminum alloy to form a die-cast aluminum alloy melt, and injecting the die-cast aluminum alloy melt into the mold for extrusion casting on the composite surface to form the die-casting component.
10. The preparation method according to claim 9, characterized in that: The parameters of the squeeze casting are: filling speed 150-200 mm / s, casting pressure 140-190 MPa, mold temperature 300-350° C., and holding time 10-30 s.
Citation Information
Patent Citations
method FOR PREVENTING TOTAL EXTRUSION OF A BILLET DURING HYDROSTATIC EXTRUSION
BE780055A
High-strength aluminum alloy semisolid pressure casting method for automobile parts
CN107245589A
Semi-solid state rheological die-casting forming method for aluminum alloy calipers
CN109926557A
Pouring gate system for preparing plate-shaped casting and semi-solid die-casting forming process
CN112338162A
Preparation method of battery end plate with insert
CN112496306A
